THE CONSEQUENCES OF OPEN DEFECATION PRACTICE IN SOUTH EAST, NIGERIA - C. Ukpabi, Monday (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the consequences of open defecation practices in Southeast Nigeria utilizing a mixed-methods research design. Quantitative data were collected through questionnaires distributed among a broad adult population, while qualitative insights were obtained via in-depth interviews with community stakeholders. This study focused on six communities in the states of Ebonyi, Enugu, and Imo, which were identified as highly affected by open defecation according to the 2019 UNICEF report and the 2011 Multi-Indicator Cluster Survey. A sample size of 1,049 was determined using Taro Yamane’s formula, and a multistage cluster sampling technique was employed. Data collection involved structured questionnaires addressing sociodemographic factors and specific research objectives and IDIs providing detailed qualitative insights. Quantitative data were analysed using SPSS version 20, descriptive statistics and inferential statistics were applied, while qualitative data were thematically analysed. The findings revealed that open defecation significantly contributes to waterborne diseases, environmental degradation, social stigmatization, and economic burdens. It also undermines educational outcomes. The study recommended government-led public health campaigns, investment in sanitation infrastructure, and community engagement programs such as Community-Led Total Sanitation (CLTS) to promote behavioural change and improve sanitation practices.